2016
DOI: 10.3389/fncel.2016.00254
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure-Induced mtDNA Alterations in Retinal Ganglion Cells and Subsequent Apoptosis

Abstract: Purpose: Our previous study indicated that mitochondrial DNA (mtDNA) damage and mutations are crucial to the progressive loss of retinal ganglion cells (RGCs) in a glaucomatous rat model. In this study, we examined whether high pressure could directly cause mtDNA alterations and whether the latter could lead to mitochondrial dysfunction and RGC death.Methods: Primary cultured rat RGCs were exposed to 30 mm Hg of hydrostatic pressure (HP) for 12, 24, 48, 72, 96 and 120 h. mtDNA alterations and mtDNA repair/repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Intraocular pressure (IOP) elevation is considered to be the major risk factor for glaucoma and so far the only treatable factor 2 . However, lowering IOP is not always sufficient to prevent progression of glaucomatous optic neuropathy 3 . Recent studies have shown that impairment of mitochondrial dynamics may play a key role in glaucomatous RGC loss 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Intraocular pressure (IOP) elevation is considered to be the major risk factor for glaucoma and so far the only treatable factor 2 . However, lowering IOP is not always sufficient to prevent progression of glaucomatous optic neuropathy 3 . Recent studies have shown that impairment of mitochondrial dynamics may play a key role in glaucomatous RGC loss 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…These changes include increased apoptosis, changes in cell morphology and gene expression. Neuronal cells including PC12 (Agar et al, 2000; Tök et al, 2014) and RGC-5 cell lines (Agar et al, 2006; Ju et al, 2009a; Ju et al, 2007; Lee et al, 2010; Liu et al, 2012), primary cultures of RGC (Sappington et al, 2006; Zhang et al, 2016), optic nerve head astrocytes (Liu and Neufeld, 2001; Liu and Neufeld, 2003; Mandal et al, 2010; Miao et al, 2010; Ricard et al, 2000; Salvador‐Silva et al, 2004; Salvador‐Silva et al, 2001; Tezel et al, 2001; Yang et al, 2004), Müller cells (Yu et al, 2012a; Yu et al, 2011; Yu et al, 2012b), or microglial cells (Madeira et al, 2015; Sappington and Calkins, 2006; Sappington and Calkins, 2008), and more complex preparations such as organotypic co-cultures of the retinal cells (Obazawa et al, 2004; Osborne et al, 2015; Tezel and Wax, 2000) or eye cup preparations (Ishikawa et al, 2010; Ishikawa et al, 2011; Reigada et al, 2008; Zhang et al, 2007) have been exposed to elevated pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial membrane potential (∆ψm) was evaluated using MitoProbe JC-1 dye (Invitrogen, Carlsbad, CA, USA) as previously described (Zhang et al, 2016 ). In brief, RGCs with different treatments were incubated with JC-1 at 37°C for 30 min while protected from light and assessed via FACS (Becton Dickinson, San Jose, CA, USA) and a confocal fluorescence microscope (Leica; green: 488 nm excitation/530 nm emission; red: 550 nm excitation/590 nm emission).…”
Section: Methodsmentioning
confidence: 99%